Prevention of Propofol Injection-Induced Pain, USing Lignocaine in large Volume: A Prospective " Randomized Double-Blind Study - Hossain, Muhammad Sazzad; Rahman, Md Afzalur; Alamgir, Md Mahiuddin; Waliullah, Md; Mandal, Muhammad Alamgir (KYAMC Journal, 2018)
a